1976
DOI: 10.1172/jci108301
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of thyroxine-binding globulin in man. Abnormal rate of synthesis in inherited thyroxine-binding globulin deficiency and excess.

Abstract: A B S T R A C T It has been previously suggested that inherited thyroxine-binding globulin (TBG) abnormalities in man may be due to mutations at a single X-chromosome-linked locus controlling TBG synthesis. However, abnormalities in TBG degradation have not been excluded. The availability of purified human TBG and its successful labeling with radioiodide allowed us to examine such possibility.Human TBG was purified by affinity chromatography, labeled under sterile conditions with 'I or 'I, and mixed with ['I]t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…non-steady state conditions, the availability of free T 4 and T 3 for deiodination could fluctuate, resulting in different T 3 /T 4 ratios independent of 5 0 -deiodinase activity. However, it seems safe to assume that steady state was achieved, since we studied the subjects after 8 weeks of sex-steroid administration, which is more than five times the half-life of T 4 and TBG (10).…”
Section: Discussionmentioning
confidence: 99%
“…non-steady state conditions, the availability of free T 4 and T 3 for deiodination could fluctuate, resulting in different T 3 /T 4 ratios independent of 5 0 -deiodinase activity. However, it seems safe to assume that steady state was achieved, since we studied the subjects after 8 weeks of sex-steroid administration, which is more than five times the half-life of T 4 and TBG (10).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, it has been postulated that these X-chromosome-linked TBG abnormalities represent either mutations of a gene regulating TBG synthesis (6) or subtle structural gene mutations that indirectly affect the rate of TBG synthesis (1). In 1981, Dick and Watson (8) reported that 40% of Australian Aborigines have low serum T4 concentration due to a variant TBG (TBG-A) with low affinity for T4.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a simultaneous rise in the serum concentrations of CBG and TBG, two other hepatic carrier proteins. The production of TBG is decreased by excess triiodothyronine (T3) (12) and its half-life is decreased in hyperthyroidism (13). Thyroid hormones may (6) or may not (14) influence the production of their own main carrier protein by a modulatory effect of T3 on TBG mRNA synthesis (6).…”
Section: Resultsmentioning
confidence: 99%